An aptamer interacting with heat shock protein 70 shows therapeutic effects and prognostic ability in serous ovarian cancer - Chang-Ni Lin; Yi-Cheng Tsai; Ching-Cheng Hsu; Yu-Ling Liang; Yi-Ying Wu; Chieh-Yi Kang; Chun-Hong Lin; Pang-Hung Hsu; Gwo-Bin Lee; Keng-Fu Hsu (Elsevier, 2021)
Ovarian cancer (OvCa) is the most lethal gynecologic malignancy owing to its high chemoresistance and late diagnosis, which lead to a poor prognosis. Hence, developing new therapeutic modalities is important for OvCa patient treatment. Our previous results indicated that a novel aptamer, Tx-01, can specifically recognize serous carcinoma cells and tissues. Here, we aim to clarify the clinical role and possible molecular mechanisms of Tx-01 in OvCa. Immunostaining and statistical analysis were performed to detect the interaction of Tx-01 and heat shock protein 70/Notch1 intracellular domain (HSP70/NICD) in OvCa. The in vitro and in vivo experiments were carried out to demonstrate the potential mechanisms of Tx-01. Results show that Tx-01 reduced serous OvCa OVCAR3 cell migration and invasion and inhibited HSP70 nuclear translocation by interrupting the intracellular HSP70/NICD interaction. Furthermore, Tx-01 suppressed serous-type OVCAR3 cell tumor growth in vivo. Tx-01 acts as a prognostic factor through its interaction with membrane-bound HSP70 (mHSP70 that locates on the cell surface without direct interaction to NICD) on ascitic circulating tumor cells (CTCs) and is reported to be involved in natural killer (NK) cell recognition and activation. Our data demonstrated that Tx-01 interacted with HSP70 and showed therapeutic and prognostic effects in serous OvCa. Tx-01 might be a potential inhibitor for use in serous OvCa treatment.